3D bioprinting of prevascularised implants for the repair of critically-sized bone defects. (May 2021) - Nulty, Jessica; Freeman, Fiona E.; Browe, David C.; Burdis, Ross; Ahern, Daniel P.; Pitacco, Pierluca; Lee, Yu Bin; Alsberg, Eben; Kelly, Daniel J.
Abstract: For 3D bioprinted tissues to be scaled-up to clinically relevant sizes, effective prevascularisation strategies are required to provide the necessary nutrients for normal metabolism and to remove associated waste by-products. The aim of this study was to develop a bioprinting strategy to engineer prevascularised tissues in vitro and to investigate the capacity of such constructs to enhance the vascularisation and regeneration of large bone defects in vivo . From a screen of different bioinks, a fibrin-based hydrogel was found to best support human umbilical vein endothelial cell (HUVEC) sprouting and the establishment of a microvessel network. When this bioink was combined with HUVECs and supporting human bone marrow stem/stromal cells (hBMSCs), these microvessel networks persisted in vitro . Furthermore, only bioprinted tissues containing both HUVECs and hBMSCs, that were first allowed to mature in vitro, supported robust blood vessel development in vivo . To assess the therapeutic utility of this bioprinting strategy, these bioinks were used to prevascularise 3D printed polycaprolactone (PCL) scaffolds, which were subsequently implanted into critically-sized femoral bone defects in rats. Micro-computed tomography (µCT) angiography revealed increased levels of vascularisation in vivo, which correlated with higher levels of new bone formation. Such prevascularised constructs could be used to enhance the vascularisation of a range of large tissue defects, forming the basis of multiple new bioprinted therapeutics. Statement of significance: This paper demonstrates a versatile 3D bioprinting technique to improve the vascularisation of tissue engineered constructs and further demonstrates how this method can be incorporated into a bone tissue engineering strategy to improve vascularisation in a rat femoral defect model. Graphical abstract: Image, graphical abstract